2015
DOI: 10.1155/2015/297239
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Morphological Correlations before and after Video-Documented 23-Gauge Pars Plana Vitrectomy with Membrane and ILM Peeling in Patients with Macular Pucker

Abstract: Purpose. To assess functional and morphological alterations following video-documented surgery for epiretinal membranes. Methods. Forty-two patients underwent video-documented 23-gauge vitrectomy with peeling of epiretinal (ERM) and inner limiting membrane (ILM). Patient assessment was performed before and 3 and 6 months including best corrected visual acuity (BCVA), slit lamp biomicroscopy, SD-OCT, and central 2° and 18° microperimetry. In addition, all video-documented areas of peeling on the retinal surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…[ 32 ] The reason for this could be that the mechanical microscopic trauma of ERM-ILM peeling caused by the use of intraocular forceps affects the outer retinal structure through the Muller cells. [ 36 , 37 ] Nevertheless, these changes seem to have no significant impact on postoperative functional outcome. [ 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 32 ] The reason for this could be that the mechanical microscopic trauma of ERM-ILM peeling caused by the use of intraocular forceps affects the outer retinal structure through the Muller cells. [ 36 , 37 ] Nevertheless, these changes seem to have no significant impact on postoperative functional outcome. [ 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the mean BCVA in all 65 patients was 0.30 ± 0.13 logMAR, and was found to be worse than in patients with separate ERM or VMT [23,24,25,26]. Further analysis of our results showed that, in the cases where VMT and ERM were unified (group I), the BCVA was statistically significantly lower than in patients with no intercorrelation between VMT and ERM (group II).…”
Section: Discussionmentioning
confidence: 39%
“…Previous studies focusing on the changes of BCVA in the presence of ERM and VMT have reported a BCVA of about 0.28 logMAR in cases with VMT alone [23]; in patients with ERM alone, it has ranged from 0.6 ± 0.2 to 0.28 logMAR [24,25,26]. In our study, the mean BCVA in all 65 patients was 0.30 ± 0.13 logMAR, and was found to be worse than in patients with separate ERM or VMT [23,24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Vitrectomy [2] is a surgery to remove some or all of the vitreous humor from the eye, to restore the light path and the eye function. It is now a routine clinical operation for various eye disorders such as diabetic eye disease (diabetic retinopathy) [3][4][5], retinal detachments [6][7][8][9][10], macular hole [11][12][13] and macular pucker [14,15]. However, due to the anatomical location of the vitreous body and the complexity of the operation, the patients tend to develop various psychological disorders before and upon the operation, which would negatively affect the therapeutic effects and their eyesight recovery.…”
Section: Introductionmentioning
confidence: 99%